The Gender Gap in Household Bargaining Power: A Revealed-Preference Approach - Gu, Ran; Peng, Cameron; Zhang, Weilong (Review of Financial Studies, 2026)
Abstract When members of the same household have different risk preferences, whose preference matters more for investment decisions and why? We propose an intrahousehold model that aggregates individual preferences at the household level as a result of bargaining. We structurally estimate the model, analyze the determinants of bargaining power, and find a significant gender gap. Gender differences in individual characteristics, as well as gender effects, partially explain the gap. These patterns hold broadly across Australia, Germany, and the United States. We further link the distribution of bargaining power to households’ perceived gender norms in a cross-sectional analysis. (JEL G11, G41, G50)